Association of viral load and ALT level among HCV-infected Bangladeshi patient with different genotypes (Bangladesh Journal of Medical Microbiology, 2017)
Hepatitis C virus (HCV) causes chronic infections that mainly affect the liver leading to hepatic fibrosis followed by development of cirrhosis and hepatocellular carcinoma (HCC). Several factors including HCV genotype have been proposed to associate with the clinical outcome of HCV infection.This study was aimed to determine whetherthere is any significant differencein HCV viral load and Alanine Aminotransferase (ALT) in relation to genotypesin HCV infected Bangladeshi patients.After quantification of HCV viral load, 36 samples were randomly selected for HCV genotyping and ALT measurement.Themean HCV viral load of genotype 1 infected patients was 14.11±6.77[log10 (copies/ml)] while it was 12.80±2.05[log10 (copies/ml)] for genotype 3 infected patients. The mean ALT level of genotype 1 and genotype 3 infected patients were 51.2±34.4 U/L and 89.6±86.6U/L respectively. There was no significant statistical difference in serum ALT or plasma viral load between genotype 1 and genotype 3 infected patients.In HCV infection, genotype may have no relation to viral load and serum ALT level among Bangladeshi patients.Bangladesh J Med Microbiol 2017; 11 (1): 14-18